PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK DI KELAS XI SMA PERTIWI 1 PADANG - Elisman, Nur Fauziah (Departemen Matematika, 2024)
Finding out how well kids learn mathematics using the Two Stay Two Stray (TSTS) Cooperative Learning Model is the main goal of this project. It will also find out whether the TSTS Model or the Conventional Learning Model is better at improving students' understanding of mathematics. In the even semester of 2023–2024, a total of 244 fifth graders from SMA Pertiwi 1 Padang were included in the study. Students in MIPA 3 and 4 from grade XI took part in the research. Participants were chosen by a straightforward random selection procedure. In this investigation, a separate posttest was administered to the control group. Mathematical tests were used to gauge competence in the research. The data from a test measuring understanding of a mathematical concept did not follow a normal distribution, thus the Mann Whitney test was used to examine the results. The TSTS has been found to enhance mathematical understanding, according to the results from the quizzes. Using a significance level of 0.05, the determined P-value from hypothesis testing was 0.000, which means that the null hypothesis (H0) is rejected. According to the results, TSTS students outperformed their Conventional Model counterparts in terms of conceptual comprehension of mathematical subjects. Students' understanding of mathematical ideas can be enhanced through the use of TSTS cooperative learning approaches.Keywords – Conventional Learning Model, Mathematics Conceptual Understanding, TSTS Model